JAS JÚZIWSHILERDIŃ KÓP JÍLLÍQ TAYARLÍQ BAǴDARLARÍ - Ilyasov, B.X. (SCIENCE and SOCIETY, 2023)
The article describes the methodical rules that determine the main directions in the blind annual training of young swimmers, the organization of sports training, and the experiences conducted in this regard among athletes. The opinions in the article are scientifically based and commented in the prescribed order.